Bioleaching as a biotechnological tool for metal recovery: from sewage to space mining - Abraham, Archana Paimpillil; Schopf, Simone (Frontiers in Bioengineering and Biotechnology, 2026)
Heavy metals are essential for technological and economic growth but can cause serious environmental and health problems due to their toxicity and persistence. Traditional methods for metal recovery often have high costs and can create secondary pollution. Bioleaching offers a sustainable, low-energy, and eco-friendly alternative, effectively recovering metals from low-grade ores and various waste materials. Recovering metals from secondary sources such as industrial and electronic waste reduces the need for new mining, thus conserving natural resources and supporting circular economic goals. Recently, biomining has expanded beyond Earth, showing promising results in space environments. This review discusses the current understanding of bioleaching processes, their potential for sustainable metal recovery on Earth and in space, their challenges, and future perspectives. Overcoming technical challenges, such as raw material composition, slow reaction kinetics, optimization of process parameters, and addressing safety concerns is crucial. A further increase in research focus aiming at scaling up bioleaching technology is essential, alongside addressing ethical and economic concerns related to space mining.